Differentiated diagnostic and surgical algorithm for isolated and combined Chiari malformation Type I - Diusheev, Buranbek; Akmataliev, Akylbek; Turdugulov, Chyngyz; Kachiev, Nurlan (Gaceta Médica de Caracas, 2023)
Introduction: Arnold-Chiari malformation (ACM) type I is a craniovertebral junction pathology with ectopy of the cerebellar tonsils through the great occipital foramen with compression of the brain stem and upper cervical spinal cord. Until now, there have been more than 20 types of surgical interventions for the Arnold-Chiari malformation type. Objective: The main purpose of this research is the decompression of craniovertebral stem structures and occipital foramen, and the search for effective methods to repair cerebrospinal fluid (CSF) circulation. Methods: The complex examination and surgical treatment at the Neurosurgery Department No. 1 of the National Hospital of the Ministry of Health of the Kyrgyz Republic (Bishkek, Kyrgyzstan) passed 201 patients (aged 16-74) with symptomatic ACM I from 2008 to 2020.